PENGARUH PEMANFAATAN SERBUK KAYU SEBAGAI MODEL MOLEKUL TERHADAP PEMAHAMAN LEVEL MIKROSKOPIK SISWA PADA MATERI HIDROKARBON - Zulkifli Zulkifli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was instigated by the low result of most student in chemistry learning at Senior High School 1 Tebing Tinggi from the microscopic aspect, specially on hydrocarbon lesson. This research aimed at knowing whether there was an effect of utilizing sawdust as molecular model toward student microscopic comprehension level on Hydrocarbon lesson. Quasi-Experiment method was used in this research with Pretest Posttest Control Group design. Simple Random Sampling was used in this research. The samples were the eleventh-grade students of MIA 2 as the control group and the students of MIA 4 as the experimental group. The instrument used was multiple choice test. The research findings showed that tobserved was 4.11 and ttable was 2.00, tobserved was higher than ttable, and it showed that there was an effect of utilizing sawdust as molecular model toward student microscopic comprehension level 21.4%Keywords : Sawdust Utilization, Molecular Model, Microscopic Level, Hydrocarbon